Investigación De Las Actitudes De Los Productores Ganaderos En La Implementación De Los Sistemas Silvopastoriles En El Cantón Joya De Los Sachas - Marcillo, Raúl Lorenzo González (European Scientific Journal, ESJ, 2018)
This paper focuses on analyzing the level of implementation of silvopastoral options as part of livestock production systems in Joya de los Sachas, Orellana, Ecuador. The attitudes of producers about the silvopastoral systems and the factors that influence the decisions and actions related to the use of this type of production systems were explored. The research shows that the producers’ decision-making process can be explained through the analysis of natural resource management problems. This was performed based on a theoretical framework of complex systems and classical institutional economics. In this research, both qualitative and quantitative methods were used in data collection and analysis. All the producers in the sample have positive attitudes toward the implementation of silvopastoral systems, which is proven by the existence of at least one silvopastoral option in their production systems. However, the levels of implementation show great variation among producers. The decisions of producers are explained by a combination of factors. In order to promote the implementation of this technology, it is important to have a dialogue with producers and understand their motivations. No biophysical factors were observed that seem to limit the level of implementation. This fact makes the potential of diversified silvopastoral systems very promising in livestock farms.